(untitled) (Ozone Therapy Global Journal, 2013)
This review summarizes the bases of the use of ozone in wound healing in patients sufferin g from trauma or burns. Di fferent clinical assays had shown that lo cal or systemic application of oxygen-ozone therapy in wounds and superficial scalds results in accelerated cleansing of a wound from necrotic tissues without generate necrosis. In addition to the well know germicide effect of ozone, its application can stimulate the local tissue regeneration, the local immune response and can control the inflammatory reaction. The quick management of pain and edema, the reduction of epithelialization time and the better graft retention are part of the benefit of the integrative use of ozone in traumatology and burns treatment. Bases on the Russ ian clinical experience the indication, contrai ndication, protocols and specific care during the application of this therapy was described. The systemic ozone therapy conducted af ter an analy sis of the oxidative str ess status in those patients was referred. The concept of integration of ozone therapy as part of the routing care of the wounds is expressed. In this context the application of ozone offer many advantages, for instance: ozone reactivating the oxygen homeostasis, can increase the antioxidant ac tivity of blood pla sma, im prove periph eral circu l atio n and microcircu l atio n, induce homeost asis compens ation, and modulate the antiinflammatory and immune response in addition to their detoxification effects